Ten years of the Recognition Act : a transparent and low-threshold structure of provision has been the key success factor - Elsässer, Johanna [Verfasser]; Wiemers, Daniela [Verfasser] (My University, 2022)
"The Recognition Act was described as a “milestone of integration policy” when it entered into force in the spring of 2012. The aims of the new statutory provisions were to help people with foreign professional and vocational qualifications to obtain appropriate employment and contribute towards securing a supply of skilled workers. To what extent has success been achieved? This article mainly focuses on the support structures that have been put in place to implement the law. It concludes by outlining the possible future development of these structures." (BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; 370; Auslandsqualifikation; Anerkennungsgesetz